Analysis of Agricultural Food Crop Productivity Planning District-District in East Java Province of Indonesia with A Non-Parametric Approach - Abid Muhtarom; Tri Haryanto; Nurul Istifadah (MediaTrend, 2019)
The importance of food crop agriculture efficiency could be used today. Because we know that more inefficiencies in the agricultural sector of food crops illustrate that productivity has not run maximally. DEA is used in this study as an appropriate approach by using a non-parametric method. The production unit is in the form of a decision making unit (DMU) in which the DMU in this study is a food crop agricultural sub-sector in 29 districts in East Java. There occurred inefficiency of as many as 44.8 percent (29 districts) in East Java in 2017 for having the average efficiency score of less than 0.69, while the rest achieved the average technical efficiency of more than 0.31.